Innovation profile of feed pelletizing technology - Rudiger, Udo; Dhehibi, Boubaker; Frija, Aymen; Elayed, Monia (International Center for Agricultural Research in the Dry Areas, 2023)
Compressing agro-industrial by products into nutrient dense livestock feed pellets is a worthwhile innovation to compete with expensive and imported feed pellets. This innovation consists of a small-scale compressor 'pelletizer' and formulas to create qualitatively suﬃcient feed pellets with local available inputs. In Tunisia, there are many agro-pastoralists that are dependent on expensive and imported livestock feed pellets to improve livestock quality and to supplement fodder shortages. Risks of relative food shortages are likely to increase due to climate change. Also, there are many discarded by-products from (local) agro-food supply chains such as olive cakes and cactus pe el, which still contain nutrients. The International Center of Agricultural Research in Dry Area saw an opportunity in the two above-explained issues and tested imported small scale pelletizing machines which were able to compress nutritious by-products into pellets. These machines are imported via Juhaina company and available for Tunisian farmers. In addition to the machine, ICARDA experimented with feasible inputs and diﬀerent ratios, considering local availability as well. It achieved highly dense and nutritious feed pellets from local available inputs, with similar or better quality than the imported pellets. The innovation profile describes the pelleting technology and evaluates its readiness level.